Analisis Pengaruh Variasi Kecepatan Motor dan Struktur Spesimen Terhadap Respon Getaran pada Shaker Table Vibration Testing Machine 3-Axis - Alfan Arfian; Abdi, Ferly Isnomo; Widoretno, Yustin Setiya; Puspitasari, Dewi (Universitas Negeri Surabaya, 2025)
Vibration testing is important to avoid uncontrolled vibrations and can cause structural and mechanical failures in machinery. Vibration testing using a laboratory-scale 3 axis shaker table vibration testing machine aims to determine the dynamic characteristics and resistance of a wind turbine structure modeled into a specimen to vibration. This research uses an experimental method by making a specimen model that has 3 structural variations, namely a plain structure, a multilevel structure, and a taper structure. This research also varies the motor rotation speed using a dimmer. There is an MPU 6050 accelerometer sensor and uses PLX-DAQ software connected to Excel for the data collection process. The results obtained 1 stable specimen model, namely the plain structure. The plain structure with a speed of 250 rpm on the X axis has a minimum acceleration value of -0.01 m/s2 and a maximum of -0.27 m/s2, on the Y axis has a minimum acceleration value of 0.00 m/s2 and a maximum of 0.27 m/s2, and on the Z axis has a minimum acceleration value of -0.06 m/s2 and a maximum of 0.27 m/s2. The plain structure with a speed of 350 rpm on the X axis has a minimum acceleration value of -0.02 m/s2 and a maximum of -0.36 m/s2, on the Y axis has a minimum acceleration value of 0.00 m/s2 and a maximum of -0.38 m/s2, and on the Z axis has a minimum acceleration value of 0.19 m/s2 and a maximum of 0.40 m/s2. Indicates that the motor speed and specimen structure model affect the vibration response because the greater the motor rpm, the higher the resulting acceleration value.